Exploring of the use of Political Correctness in World - Akmal Wisnu Yuwana; Widya Cathrine (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
As we understand, the use of political correctness is mainly to avoid and reduce the gap with those who are underprivileged in society. The more awareness that people have about PCs, the more peaceful life is because it avoids awakening of superiority and a sense of indifference. Though there are some controversies behind the banner of political correctness. Thus knowing political correctness is a double-edged sword when establishing communication with others. In this study, we aimed to investigate the use of political correctness in the current situation to increase knowledge among people during the running globalization times. Using sources from around the internet, we tried to uncover the impact of the political correctness world at large. This is qualitative research using library research to define what the role of Political Correctness in the world is.